Concepts, Methods and Applications of Quantum Systems in Chemistry and Physics Selected proceedings of QSCP-XXI (Vancouver, BC, Canada, July 2016) - Wang, Yan A.; Thachuk, Mark.; Krems, Roman; Maruani, Jean.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This edited, multi-author volume contains selected, peer-reviewed contributions based on the presentations given at the 21th International Workshop on Quantum Systems in Chemistry, Physics, and Biology (QSCP-XXI), held in Vancouver, Canada, in July 2016.  This book is primarily aimed at scholars, researchers and graduate students working at universities and scientific laboratories and interested in the structure, properties, dynamics and spectroscopy of atoms, molecules, biological systems and condensed matter.
Quantum Chemistry Methodology -- Molecular Structure and Dynamics -- Biochemistry and Biophysics -- Fundamental Theory.
Keywords: Chemistry, Physical and theoretical; Atomic structure .; Molecular structure .; Bioinformatics; Quantum physics; Surfaces (Physics).; Theoretical Chemistry; Atomic and Molecular Structure and Properties; Computational and Systems Biology; Quantum Physics; Surface and Interface and Thin Film